CPIXE and Projections for Energy Prices - Einar W. Nordbø (Norges Bank, 2008)
This paper describes the new indicator of underlying inflation used at Norges Bank, the consumer price index adjusted for tax changes and excluding temporary changes in energy prices (CPIXE). In particular, we discuss the projections for energy prices, which impact on the estimated trend change in energy prices in the CPIXE.
hdl:11250/2507961
Keywords: 330